2006
DOI: 10.1016/s1542-3565(05)00746-9
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography to Identify Intramucosal Carcinoma and High-Grade Dysplasia in Barrett’s Esophagus

Abstract: Background & Aims-Optical coherence tomography (OCT) is an optical technique that produces high-resolution images of the esophagus during endoscopy. OCT can distinguish specialized intestinal metaplasia (SIM) from squamous mucosa, but image criteria for differentiating intramucosal carcinoma (IMC) and high-grade dysplasia (HGD) from low-grade dysplasia (LGD), indeterminate-grade dysplasia (IGD), and SIM without dysplasia have not been validated. The purpose of this study was to establish OCT image characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
179
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(187 citation statements)
references
References 29 publications
4
179
0
4
Order By: Relevance
“…The overall average accuracy achieved by the readers was 82.6% (range, 73.7-94.7%), with good sensitivity (80.3-85.7%) and specificity (83.3-97.6%) for each of the carcinoma types over the two validation assessments. The sensitivities and specificities achieved in this study are comparable to those reported in prior studies validating OCT criteria in esophageal (23,24) and cardiovascular pathology (19).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The overall average accuracy achieved by the readers was 82.6% (range, 73.7-94.7%), with good sensitivity (80.3-85.7%) and specificity (83.3-97.6%) for each of the carcinoma types over the two validation assessments. The sensitivities and specificities achieved in this study are comparable to those reported in prior studies validating OCT criteria in esophageal (23,24) and cardiovascular pathology (19).…”
Section: Discussionsupporting
confidence: 84%
“…OCT can be used to conduct large-volume in vivo microscopy of tissue with resolutions comparable to low-power microscopy (18). OCT has been used to accurately detect and diagnose pathology in vivo for a number of years (17)(18)(19)(20)(21)(22)(23)(24) and has been used to assess the fine microarchitectural features in both normal and pathologic lung (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%
“…2 In addition, it has been developed for application in cardiovascular, gastroesophageal, and cancer imaging. 3 OCT has also found application beyond the medical field, in areas such as metrology, non-destructive testing, microfluidics, and others. 4 As in other 3-D optical imaging modalities, OCT suffers from reduced depth-of-field when increasing the numerical aperture (NA) of the imaging system.…”
mentioning
confidence: 99%
“…OCT is promising in many fields of cancer diagnosis, especially where excisional biopsy or another invasive method is typically used but undesirable [223]. OCT is endoscope-compatible [41] and thus well suited to examine hollow organs like the gastrointestinal tract [224][225][226], the bronchi [227] and the urinary bladder [228]. Subcutaneous imaging needles [42,229,230] and forward imaging probes [231][232][233] provide further possibilities to apply OCT for minimally invasive examination.…”
Section: Emerging Medical Applicationsmentioning
confidence: 99%